Courtship behavior of different wild strains of Ceratitis capitata (Diptera: Tephritidae) - Briceño, D. (2007)
This study documents differences in the courtship behavior of wild strains of Ceratitis capitata (Wiedemann) from Madeira (Portugal), Hawaii (U.S.A.), Costa Rica, and Patagonia (Argentina). Some traits showed large variations and others substantial overlaps. The angle at which the male faced toward the female at the moment of transition from continuous wing vibration and intermittent buzzing changed very little during the course of courtship in all strains, but males from Madeira tended to face more directly toward the female than other males. Females tended to look more, and more directly, toward the males as courtship progressed in all strains. The distance between male and female tended to decrease as courtship proceeded in all strains, but the distances at which males initiated continuous vibration, intermittent buzzing, and jumped onto the female were relatively less variable between strains, except for the strain from Costa Rica. Flies of Madeira courted for longer and the male moved his head and buzzed his wings longer than the other strains.